The relationship between dietary flavonoid intake and hypertension: a cross-sectional study from NHANES - Niu, Yueyue; Chen, Xingjuan; Xiao, Lu; Li, Weina; Feng, Ling; Aierken, Aikeremu (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo evaluate the association between dietary flavonoid intake and hypertension using nationally representative data, considering increasing global hypertension prevalence and inconsistent evidence on flavonoids’ protective effects.MethodsThis cross-sectional study analyzed 8,054 adults aged ≥20 years from NHANES 2007–2010 and 2017–2018. Flavonoid intake was assessed through two 24-hour dietary recalls and categorized into quartiles. Hypertension was defined by blood pressure ≥130/80 mmHg or self-reported diagnosis/medication use. Logistic regression models with progressive adjustment, restricted cubic spline regression for dose-response relationships, and subgroup analyses were conducted, accounting for complex sampling design.ResultsAfter full adjustment, participants in the highest quartile of total flavonoid intake showed 25% lower odds of hypertension compared to the lowest quartile (OR = 0.75, 95% CI: 0.60–0.93, p = 0.01). Among flavonoid subclasses, anthocyanidins (OR = 0.74, 95% CI: 0.58–0.93) and flavan-3-ols (OR = 0.76, 95% CI: 0.62–0.93) demonstrated the strongest protective associations. Significant effect modifications were observed for age (p for interaction = 0.01), hyperlipidemia (p for interaction <0.0001), and cardiovascular disease status (p for interaction =0.01), with stronger protective effects in younger adults and those without metabolic disorders.ConclusionModerate dietary flavonoid intake, particularly anthocyanidins and flavan-3-ols, is inversely associated with hypertension risk. These associations vary significantly by age and metabolic status, suggesting potential for individualized dietary recommendations for hypertension prevention.